Kesulitan Guru Bahasa Inggris dalam Menggunakan E- Learning Selama Pandemi Covid-19 - Marzuki Marzuki; Ismail Yunus H; Agung Rinaldy Malik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the difficulties of English teachers in using e-learning during the Covid-19 pandemic. This research uses qualitative research. The participants were 10 English teachers from different high schools in Tolitoli Regency, Central Sulawesi. The instruments used to collect data were questionnaires and interviews according to the topic. These findings reveal that English teachers experience three obstacles during online learning, including knowledge about the use of e-learning, quality of internet connection, and physical condition. Keywords: Teacher, e-learning, Covid-19 Pandemic